Neo-victorian biofiction : reimagining nineteenth-century historical subjects - Kohlke, Marie-Luise; Gutleben, Christian (Neo-Victorian series ;, 2020)
"This volume explores the many paradoxes of neo-Victorian biofiction, a genre that yokes together the real and the imaginary, biography and fiction, and generates oxymoronic combinations like creative facts, fictional truth, or poetic truthfulness. Contemporary biofictions recreating nineteenth-century lives demonstrate the crucial but always ethically ambiguous revision and supplementation of the historical archive. Due to the tension between ethical empathy and consumerist voyeurism, between traumatic testimony and exploitative exposé, the epistemological response is per force one of hermeneutic suspicion and iconoclasm. In the final account, this volume highlights neo-Victorianism's deconstruction of master-narratives and the consequent democratic rehabilitation of over-looked microhistories"--